Поширення пшенично-житньої транслокації в зразках пшениці м’якої озимої (Triticum aestivum L.) української селекції - Зайцева, Г.П.; Акініна, Г.Є.; Твердохліб, О.В.; Попов, В.М. (Фактори експериментальної еволюції організмів, 2015)
Aims. The aim of our research was identification of wheat-rye translocation in soft winter wheat samples of Ukrainian breeding. Methods. DNA was isolated from a mixture of five seeds. Presence of wheat-rye translocation was studied by polymerase chain reaction (PCR). Results. To identify wheat-rye translocations used two types of DNA markers – RIS and SCM 9. The presence of RIS-marker indicates the presence of rye short chromosome arm 1RS in wheat genome, SCM9-marker indicates localization of rye translocation in wheat genome – 1BL or 1AL chromosome. Conclusions. We revealed 1RS rye translocation in following samples of soft winter wheat: line 808/10 and varieties Al’ians, Doridna (the Plant Production Institute nd. a. V.Ya. Yuriev); Kryzhynka, Favorytka and Spasivka (the Mironivskiy Institute of wheat nd. a. V.M. Remeslo). The 1RS translocation in 1BL wheat chromosome was identified in varieties Doridna, Kryzhynka, Favorytka and line 808/10. The presence of rye translocations in 1AL wheat chromosome was revealed in variety Spasivka. We did not identify rye translocation in wheat samples of Odessa breeding. Keywords: wheat-rye translocation, DNA markers, T. aestivum L.